Seroprevalence of Hepatitis A and Associated Socioeconomic Factors in Young Healthy Korean Adults (Gut and Liver, 2011)
Background/Aims: An epidemiologic shift of hepatitis A virus (HAV) seroprevalence is expected due to an improvement in socioeconomic status in young adults in Korea. We investigated the age-specific seroprevalence and socioeconomic factors associated with HAV seropositivity in young, healthy Korean adults. Methods: Between March 2009 and February 2010, a total of 5,051 persons from 20 to 49 years of age presenting for a health check-up were included and responded to a questionaire. The seroprevalence of HAV was investigated by measuring immunoglobulin G (IgG) anti-HAV. A total of 984 pairs of cases and age- and sex-matched controls were analyzed for associated socioeconomic factors. Results: The prevalence of seropositive HAV was 6.2% in the 20 to 29 age range, 33.1% in the 30 to 39 range and 82.4% in the 40 to 49 range (p<0.001). There were no signifi cant differences in any group according to gender. A multivariate analysis for paired cases indicated that HAV seropositivity was signifi cantly higher in the low monthly income (below five million won, approximately 4,300 dollars) group and the Helicobacterpylori (H. pylori)-positive group (odds ratio [OR], 1.65; 95% confi dence interval [CI], 1.27-2.14; p<0.001; OR, 1.45; 95% CI, 1.19-1.76; p<0.001, respectively). Conclusions: HAV seropositivity in young adults presenting for a health checkup appears to be decreasing, and the prevalence was signifi cantly higher in the low monthly income group and the H. pylori-positive group. (Gut Liver 2011;5:88-92)